Considering perspectives of others: A case study of intercultural learning among English language learners in Norway - Anastasia Hanukaev (Peoples' Friendship University of Russia (RUDN University), 2022)
The concept of perspective is embedded within the studies of culture and language, especially with regard to an intercultural orientation within EFL teaching and learning. However, researchers have rarely explored how perspective taking can be facilitated among language learners and what types of tasks can facilitate this process. This paper describes a case study in which English as a foreign language (EFL) learners (aged 14-15) engaged in focus group interviews conducted at the end of an E-portfolio of Intercultural Competence (EPIC) project. By foregrounding perspective taking within intercultural awareness, the paper explores connections between types of tasks implemented and the ways participants considered perspectives of others in their focus group interviews. The findings thus have implications for language teaching as the results highlight the need to support the pupils through adapted activities with a greater focus on the awareness of diversity of perspectives, storytelling, reading picture books, and reflection on narrative accounts of past events. In addition, an understanding of the differences and comparing ways of living of people from diverse cultures should be coupled with support from the teacher, allowing the learners to decentre from their perspectives.